Private Equity and Venture Capital in SMEs in Developing Countries : The Role for Technical Assistance - Divakaran, Shanthi; McGinnis, Patrick J.; Shariff, Masood (World Bank, Washington, DC, 2014)
This paper discusses the constraints for private equity financing of small and medium enterprises in developing economies. In addition to capital, private equity investors bring knowledge and expertise to the companies in which they invest. Through active participation on the board of directors or in partnership with management, private equity investors equip companies with critical improvements in governance, financial accounting, access to markets, technology, and other drivers of business success. Although private equity investors could help to create, deepen, and expand growth of small and medium enterprises in developing economies, the vast majority of private equity in such markets targets larger or more established enterprises. Technical assistance, when partnered with private equity, can unlock more investor commitments and considerably enhance the ability of small and medium enterprises in emerging markets to raise private equity capital. Technical assistance provides funding that allows private equity funds to extend their reach to smaller companies. Technical assistance can mitigate some level of risk and increase the probability of successful investments by funding targeted operational improvements of investee companies. Dedicated technical assistance facilities financed by third parties, such as development finance institutions, governments, or other parties, have emerged to fill this critical need. The paper discusses the provision of investment capital twinned with technical assistance, which is now more accepted by limited partners and general partners or fund managers and is becoming more of a market model for private equity finance focused on small and medium enterprises.